PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATEMATIKA DI TAMAN PURBAKALA BATU PAKE GOJENG KABUPATEN SINJAI - Nurjannah Nurjannah; Nurhalizah Nurhalizah; Eka Irmawati; Andi Auliya Ismunandar (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
The purpose of this study was to describe the integration of etnomathematics in mathematics learning; describes cultural values ​​with ornaments that are closely related to mathematics and explores and explores mathematical concepts that can be utilized as a source of learning mathematics and efforts to develop etnomathematics as a basis for learning mathematics. The data collection process was carried out using exploration methods, documentation, literature study, and observation in the Batu Pake ’Gojeng park located on Jalan Veteran, Biringere, North Sinjai, Sinjai Regency. Based on the research results, it can be concluded that the organization and buildings contained in the Gojeng Archaeological Stone Park have mathematical elements, namely building space, flat building, statistics, social arithmetic and collections. Thus, the role of ethnomatemics is as a student facility to be able to construct mathematical concepts in the park of the Archaeological Rock using Gojeng and can be used as a medium to facilitate students understanding mathematical concepts.